Transcutaneous Spinal Cord Stimulation to Stabilize Seated Systolic Blood Pressure in Persons With Chronic Spinal Cord Injury: Protocol Development - Caitlyn G. Peters; Noam Y. Harel; Joseph P. Weir; Yu-Kuang Wu; Lynda M. Murray; Jorge Chavez; Fiona E. Fox; Christopher P. Cardozo; Jill M. Wecht (Neurotrauma Reports, 2023)
Transcutaneous spinal cord stimulation (tSCS) is an emerging therapeutic strategy to target spinal autonomic circuitry to normalize and stabilize blood pressure (BP) in hypotensive persons living with chronic spinal cord injury (SCI). Our aim is to describe our current methodological approach to identify individual tSCS parameters that result in the maintenance of seated systolic blood pressure (SBP) within a pre-defined target range. The parent study is a prospective, randomized clinical trial in which eligible participants will undergo multiple mapping sessions to optimize tSCS parameter settings to promote stable SBP within a target range of 110?120?mm Hg for males and 100?120?mm Hg for females. Parameter mapping includes cathode electrode placement site (T7/8, T9/10, T11/12, and L1/2), stimulation frequency (30, 60?Hz), current amplitudes (0?120?mA), waveform (mono- and biphasic), pulse width (1000??s), and use of carrier frequency (0, 10?kHz). Each participant will undergo up to 10 mapping sessions involving different electrode placement sites and parameter settings. BP will be continuously monitored throughout each mapping session. Stimulation amplitude (mA) will be increased at intervals of between 2 and 10?mA until one of the following occurs: 1) seated SBP reaches the target range; 2) tSCS intensity reaches 120?mA; or 3) the participant requests to stop. Secondary outcomes recorded include 1) symptoms related to autonomic dysreflexia and orthostatic hypotension, 2) Likert pain scale, and 3) skin appearance after removal of the tSCS electrode. Clinical Trials Registration: NCT05180227